Revealing the nature of photoluminescence emission in the metal-halide double perovskite Cs2AgBiBr6. Issue 27 (24th June 2019) - Zelewski, S. J.; Urban, J. M.; Surrente, A.; Maude, D. K.; Kuc, A.; Schade, L.; Johnson, R. D.; Dollmann, M.; Nayak, P. K.; Snaith, H. J.; Radaelli, P.; Kudrawiec, R.; et al.
Abstract : The emission and absorption of Cs2 AgBiBr6 are dominated by the strong carriers–phonon coupling. Abstract : Double perovskite crystals such as Cs2 AgBiBr6 are expected to overcome the limitation of classic hybrid organic–inorganic perovskite crystals related to the presence of lead and the lack of structural stability. Perovskites are ionic crystals in which the carriers are expected to strongly couple to lattice vibrations. In this work we demonstrate that the photoluminescence (PL) emission in Cs2 AgBiBr6 is strongly influenced by the strong electron–phonon coupling. Combining photoluminescence excitation (PLE) and Raman spectroscopy we show that the PL emission is related to a color center rather than a band-to-band transition. The broadening and the Stokes shift of the PL emission from Cs2 AgBiBr6 is well explained using a Franck–Condon model with a Huang–Rhys factor of S = 11.7 indicating a strong electron–phonon interaction in this material.